Limited public and private space for Polish retirees - Kotlarska-Michalska, Anna (Instytut Socjologii Uniwersytet Wrocławski, 2014)
This article presents selected examples of the phenomenon of limiting social space for elderly people. This phenomenon takes the form of covert discrimination. Discrimination against Polish retirees is particularly evident in relation to such important roles as the role of the patient, employee, and social care client.
Keywords: discrimination; limiting someone’s rights; limiting the possibilities for playing social roles